Pengaruh Kepemimpinan Transformasional, Disiplin Kerja dan Kepuasan Kerja Terhadap Kinerja Guru Sekolah Menengah Kejuruan (SMK) Negeri 4 Pekanbaru - Lisna Della (PT. Karya Inovatif Nusantara, 2024)
This research aims to determine the influence of transformational leadership, work discipline and job satisfaction on teacher performance. This research uses quantitative methods and uses a Likert scale as measurement. The population used in this research were teachers at SMK Negeri 4 Pekanbaru. The research sample was 77 respondents. Data collection was carried out through questionnaires distributed to teachers at SMK Negeri 4 Pekanbaru using a saturated sampling technique. Data testing uses validity tests, reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests and determination tests with the help of SPSS 20 software. The results of this research show that transformational leadership does not have a positive and significant effect on teacher performance, work discipline has a positive effect and significant effect on teacher performance, and job satisfaction does not have a positive and significant effect on teacher performance.